Chronic kidney disease is independently associated with increased mortality in patients with nonalcoholic fatty liver disease. (4th December 2018) - Paik, James; Golabi, Pegah; Younoszai, Zahra; Mishra, Alita; Trimble, Gregory; Younossi, Zobair M.
Abstract: Background & Aims: Nonalcoholic fatty liver disease and chronic kidney disease share similar pathophysiologic features. Our aim was to assess the association between different stages of chronic kidney disease and mortality in patients with nonalcoholic fatty liver disease. Methods: Third National Health and Nutrition Examination Survey‐linked mortality files were utilized. Nonalcoholic fatty liver disease was diagnosed by hepatic ultrasound and chronic kidney disease was defined according to the Kidney Disease Improving Global outcomes guideline. Multivariable Cox proportional hazard model was used to assess the effect of chronic kidney disease on overall and cardiovascular mortality. Results: Total cohort included 11 695 adult participants; mean age 43.3 years, 48.4% male, 76.4% white, 18.6% had nonalcoholic fatty liver disease and 9.3% had chronic kidney disease. 5.6% had diabetes, 21.3% had hypertension, 4.3% had cardiovascular disease. Compared to subjects without chronic kidney disease or nonalcoholic fatty liver disease, nonalcoholic fatty liver disease patients with chronic kidney disease were more likely to be older, had less income, and higher prevalence of comorbidities (all P  < 0.001). Prevalence of chronic kidney disease among nonalcoholic fatty liver disease cohort was 11.31%. Compared to non‐nonalcoholic fatty liver disease group, patients with nonalcoholic fatty liver disease had higher rates of stage 1, 2 and 3a chronic kidney disease, but similar rates for stage 3b, 4 and 5. Mortality rate was 18.5% in 17 years. Among nonalcoholic fatty liver disease cohort, the presence of chronic kidney disease stages 2‐3a (HR = 2.31, 95% CI: 1.70‐3.15) and stages 3b‐5 (HR = 4.83, 95% CI: 2.40‐9.71) were independently associated with increased overall mortality. Conclusions: Among patients with nonalcoholic fatty liver disease, moderate to advanced stages of chronic kidney disease are associated with overall mortality. Identification of chronic kidney disease in nonalcoholic fatty liver disease has important prognostic implications.